PENGARUH KUALITAS PELAYANAN DAN FASILITAS PENDIDIKAN TERHADAP KEPAUASAN MAHASISWA IAIN KEDIRI - Oktawira Wimaputri; Sri Hastuti; Ahsin Daroini (INCARE, International Journal of Educational Resources, 2020)
Higher education is one of the important pillars that is expected to bring improvement to a nation, because higher education is to train people, sharpen and use their intelligence to solve their problems. The education level system in Indonesia has various levels of education. The purpose of this study are: (1) Testing the significance of the service quality and educational facilities simultaneously on student’s satisfaction of Tarbiyah Faculty IAIN Kediri. (2) Testing the significance of the service quality variable effect on the student’s satisfaction of Tarbiyah faculty IAIN Kediri. (3) Test the significance of the educational facilities variable effect on the student’s satisfaction of Tarbiyah faculty IAIN Kediri. This type of research is a quantitative research. The study was conducted at Tarbiyah Faculty of IAIN Kediri. The number of respondents was 100 people. The results of this study are (1) simultaneously the service quality and educational facilities have effect on student’s satisfaction (2) partially the service quality has a positive and significant effect on student’s satisfaction (3) partially the educational facilities have a positive and significant effect on student’s satisfaction